Paenibacillus alvei MP1 as a Producer of the Proteinaceous Compound with Activity against Important Human Pathogens, Including Staphylococcus aureus and Listeria monocytogenes - Magdalena Pajor; Zirui Ray Xiong; Randy W. Worobo; Piotr Szweda (Pathogens, 2020)
An emerging need for new classes of antibiotics is, on the one hand, evident as antimicrobial resistance continues to rise. On the other hand, the awareness of the pros and cons of chemically synthesized compounds’ extensive use leads to a search for new metabolites in already known reservoirs. Previous research showed that Paenibacillus strain (P. alvei MP1) recovered from a buckwheat honey sample presented a wide spectrum of antimicrobial activity against both Gram-positive and Gram-negative pathogens. Recent investigation has confirmed that P. alvei MP1 (deposited at DDBJ/ENA/GenBank under the accession WSQB00000000) produces a proteinaceous, heat-stable compound(s) with the maximum antimicrobial production obtained after 18 h of P. alvei MP1 growth in LB medium at 37 °C with continuous shaking at 200 RPM. The highest activity was found in the 40% ammonium sulfate precipitate, with high activity also remaining in the 50% and 60% ammonium sulfate precipitates. Moderate to high antimicrobial activity that is insensitive to proteases or heat treatment, was confirmed against pathogenic bacteria that included L. monocytogenes FSL – X1-0001 (strain 10403S), S. aureus L1 – 0030 and E. coli O157: H7. Further studies, including de novo sequencing of peptides by mass spectrometry, are in progress.